Restoration and conservation of Tilmen Mound ceramics - Hasgüler, Deniz Hepdinç (Institute of Archaeology and Ethnology Polish Academy of Sciences, 2017)
Tilmen Mound in the province of Gaziantep in southeastern Anatolia in Turkey was first discovered by Prof. Bahadır Alkim and his assistant Refik Duru in 1958. Excavations were carried out until 1972 and restarted in 2003 within the framework of Turkish-Italian cooperation conducted by Nicolo Marchetti from the University of Bologne; this work was continued through 2007. Restoration and conservation work was carried out on site and in the laboratory, in the latter case including ceramics from various seasons, which differed in their state of disintegration depending on how well they had been fired and the quality of the original craftsmanship. The article presents conservation practices applied to the ceramics from the Tilmen Mound and the results that were achieved
ill. ; 24 cm
Keywords: Tilmen Mound; ceramics; restoration; conservation